Jenis-Jenis Tumbuhan Parasit dan Persebarannya di Institut Teknologi Bandung (ITB) Kampus Ganesha: Parasitic Plants and Their Distributions at Institut Teknologi Bandung (ITB) Ganesha Campus - Tambunan, Meidoraeka Rigine; Raihandhany, Reza (Departemen Biologi, Institut Pertanian Bogor, 2020)
Parasitic plants are a group of plants that live and have a broad ecological distribution which in general attack trees, shrubs or herbs to be used as a host. Some parasitic plants attacked some plants in Institut Teknologi Bandung (ITB) Ganesha Campus, Bandung. Exploration and collection of these parasitic plants in this area are conducted. Three parasitic plants species, such as Cuscuta australis, Scurrula parasitica, and Dendrophthoe pentandra are recorded and they attack 7 other plants species in ITB Ganesha. S. parasitica is reported as the highest population species to parasiting 5 plants species, while C. australis only parasiting 3 plants species and D. pendantra is parasiting 4 plants.